A study to assess the effectiveness of community health nurse led educational module on modifiable risk factors of cardiovascular diseases among adults residing at selected urban areas, Chennai - Krishnamurthy, Tamilselvi; Rajendran, Shankar Shanmugam; Venkatachalam, Gomathi Priya; Narayanasamy, Vanitha; Sheriff, Dhastagir Sultan (International Journal Of Community Medicine And Public Health, 2024)
Knowledge is an important pre-requisite for implementing both primary as well as secondary preventive strategies for cardiovascular disease (CVD). There are no estimates of the level of knowledge of risk factor of heart disease in patients with CVD. Therefore, educating the public with relevant information related to cardiac health will help reduce the spread of non-communicable diseases (NCDs). One of the community-based strategy is to educate participants about cardiac health and CVD. A nurse-led intervention was carried out to bring about a change in the behaviour participants related to modifiable and non-modifiable risk factors related to CVD. The present study indicates the value of educating the public about risk factors associated with CVD.